RESEARCH ON THE RELATIONSHIP BETWEEN FRACTURE STRAIN AND TRIAXIALITY OF 6061-T6 ALUMINUM ALLOY - YI HaiJiao; ZHEN Ying; CAO YuGuang; ZHANG ShiHua; SHI YongJin (Jixie qiangdu)
It has important theoretical significance and application value for analyzing the fracture failure process of 6061-T6 aluminum alloy to study the relationship between fracture strain and stress triaxiality and establish the fracture failure model. The quasi-static tensile tests and numerical simulations of 6061-T6 aluminum alloy smooth bar specimens and notched bar specimens were carried out by means of digital image correlation（ DIC） measurement technique and Abaqus software,respectively. The stress triaxiality of the latter was analyzed and corrected based on the results obtained,and a part of the Johnson-Cook（ J-C）failure model was obtained. The relationship between the fracture strain and the stress triaxiality of 6061-T6 aluminum alloy was established. The failure model was input into Abaqus for fracture numerical simulation. The simulation results were basically consistent with the experimental results,which verified the correctness of the failure model. It’s shown that the fracture strain of6061-T6 aluminum alloy decreases with the increase of stress triaxiality,and the J-C failure model can well describe the fracture failure behavior of 6061-T6 aluminum alloy under different stress triaxiality.